Motion sickness: an overview - Alexander KC Leung; Kam Lun Hon (BioExcel Publishing Ltd, 2019)
Background: Motion sickness is a common phenomenon that affects almost everybody at some point in their lifetime. Clinicians should be familiar with the proper management of this condition. Objective: To provide an update on the current understanding of the pathophysiology and management of motion sickness. Methods: A PubMed search was performed with Clinical Queries using the key term 'motion sickness.' The search strategy included meta-analyses, randomized controlled trials, clinical trials, observational studies, and reviews. The search was restricted to English literature. The information retrieved from the earlier search was used in the compilation of the present article. Results: Motion sickness is typically triggered by low-frequency vertical, lateral, angular, rotary motion, or virtual stimulator motion, to which an individual has not adapted. Sine qua non for developing motion sickness is when the brain receives conflicting information from different sensors about real body movements or virtual environment. The principal sensors are the eyes, the vestibular apparatus, and proprioceptive receptors. The conflicting information is judged in relation to a pattern of expected associations formed under normal or experienced conditions stored in the brain. Motion sickness typically presents with malaise, anorexia, nausea, yawning, sighing, increased salivation, burping, headache, blurred vision, non-vertiginous dizziness, drowsiness, spatial disorientation, difficulty concentrating, and sometimes vomiting. Simple behavioral and environmental modifications can be effective in the prevention of motion sickness. Medications that are effective in the prophylaxis and/or treatment of motion sickness include anticholinergics, antihistamines, and sympathomimetics. Conclusion: In most cases, motion sickness can be prevented by behavioral and environmental modifications (avoidance, habituation, and minimization of motion stimuli). Pharmacotherapy should be considered in the prevention and/ or treatment of more severe motion sickness and for patients who do not respond to conservative measures. Medications are most effective when combined with behavioral and environmental modifications. Drugs that are effective in the prophylaxis and/or treatment of motion sickness include anticholinergic agents and antihistamines.